Costs, equity and acceptability of three policies to prevent obesity: A narrative review to support policy development. (10th July 2020) - Lobstein, Tim; Neveux, Margot; Landon, Jane
Summary: Obesity prevention policies are a priority for many governments and intergovernmental agencies. Policy makers not only use systematic reviews of effectiveness but also consider contextual issues including cost and cost‐effectiveness, equity, rights, acceptability and feasibility. To support their work, the present narrative review examines three contextual issues (costs, equity and acceptability) in relation to three policies for obesity prevention: sweetened beverage taxes, front‐of‐pack nutrition labelling and restrictions on advertising to children. Literature searches led to over 1100 documents, of which 125 informed the present review. Beverage taxes were found likely to be highly cost‐effective, moderately favourable for health equity, supported by the public (depending on the use of revenues) and by health professionals and civil society groups and opposed by commercial interests. Depending on the design, front‐of‐pack nutritional labelling is likely to be highly cost‐effective, moderately favourable for health equity, supported by the public, health professionals and civil society groups, and opposed by commercial interests. Restrictions on child‐directed advertising are likely to be highly cost‐effective in the longer term, moderately favourable for health equity, supported by the public, health professionals and civil society groups and opposed by commercial interests (unless voluntary). The evidence base needs strengthening, but the authors find that all three policies merit consideration by governmental authorities, and should be implemented to reduce obesity risk.